2022
DOI: 10.33019/society.v10i2.464
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance, Job Satisfaction and Performance Among Millennial and Gen Z Employees: A Systematic Review

Abstract: Although the impact of work-life balance and job satisfaction on employee performance has been extensively studied, there still lacks a comprehensive understanding of the interplay among these variables among millennials and generation Z (gen Z) employees. This present inquiry, therefore, aims to systematically analyze how work-life balance and job satisfaction affect millennials’ and gen Z’s performance. Following a systematic literature review approach, relevant studies published in 2018-2022 were derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…In line with the current results, previous studies found that students who effectively managed their time and maintained a harmonious lifestyle tended to achieve higher academic performance 29 . Furthermore, it was reported that individuals from Generation Z were more inclined to prioritize work-life balance, recognizing its pivotal role in mitigating stress and enhancing their educational experiences 30 . In contrast, it was shown that prevalence rates of work-life conflicts are above average in men and women with higher levels of education 1 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with the current results, previous studies found that students who effectively managed their time and maintained a harmonious lifestyle tended to achieve higher academic performance 29 . Furthermore, it was reported that individuals from Generation Z were more inclined to prioritize work-life balance, recognizing its pivotal role in mitigating stress and enhancing their educational experiences 30 . In contrast, it was shown that prevalence rates of work-life conflicts are above average in men and women with higher levels of education 1 .…”
Section: Discussionsupporting
confidence: 88%
“…29 Furthermore, it was reported that individuals from Generation Z were more inclined to prioritize work-life balance, recognizing its pivotal role in mitigating stress and enhancing their educational experiences. 30 In contrast, it was shown that prevalence rates of work-life conflicts are above average in men and women with higher levels of education. 1 Lunau et al 2 also demonstrated that women with tertiary education, working in low-skilled clerical or high-skilled manual jobs in large or very large firms and temporary contracts, were at higher risk of work-life imbalance.…”
Section: Educational Attainment and Wlbmentioning
confidence: 97%
“…The accepted H2 mentioned that there was a significant difference between Gen Y and Gen Z in Job Satisfaction. the results found that Gen Y have a higher Job Satisfaction (M= 264.3), these findings successfully aligned with earlier studies (Putri et al, 2019;Lever, 2022;Waworuntu et al, 2022) that reported significant generational differences in Job Satisfaction. Earlier studies showed that Gen Y was more likely to experience job satisfaction.…”
Section: The Variance Between Gen Y and Gen Zsupporting
confidence: 89%
“…Flexibility is crucial not just for achieving work-life balance but also for the job satisfaction of millennials and Generation Z. (Waworuntu et al, 2022).…”
Section: Gen Y and Gen Z Differences In Organizational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation